The Effect of Performance Assessment, Leader Positive Feedback, and Job Autonomy on Innovative Behavior - Andri Kusmayadi; Maria Kristina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Innovative employee behaviour in a company is due to employees who always develop their ideas at work as a positive reflection for other employees to produce good performance so that company goals can be achieved. The purpose of this study was to determine the effect of performance appraisal, positive feedback from leaders, and job autonomy on innovative behaviour. This study used Structural Equation Modeling analysis using a sample of 160 employees in the personnel, marketing, finance and accounting divisions at a three-wheel cement distributor. Data were analyzed using Lisrel software. The results showed that innovative behaviour could be influenced by performance appraisals, positive feedback from leaders, and job autonomy. Therefore, this study has several important managerial implications for superiors, whether adequate performance appraisal, positive feedback given by the leader, or given job autonomy will increase the innovative behaviour of employees. It is suggested that organizations need to pay attention to work autonomy which is an essential factor in improving employee appraisal. Researchers can further replicate the model in different contexts to verify its model's applicability.